Strengthening Ni-Coated CNT/Mg Composites by Optimizing the CNT Content - Jilei Xu; Yizhuang Zhang; Zhiyuan Li; Yunpeng Ding; Xin Zhao; Xinfang Zhang; Hanying Wang; Changhong Liu; Xiaoqin Guo (Nanomaterials, 2022)
The dispersion of carbon nanotubes (CNTs) is the bottleneck in CNT-reinforced metal matrix composites. In this work, CNT/Mg composites were prepared by grinding Mg powder and then dispersing CNTs via ball milling and hot pressing. The uniform distribution of Ni-coated CNTs in the matrix was achieved by optimizing the content of CNTs. Scanning electron microscope, high-resolution transmission electron microscopy and X-ray diffraction, optical microscopy, and compression tests were employed. With the CNT content being less than 1%, the CNTs can be evenly distributed in CNT/Mg composites, resulting in a sharp increase in strength. However, with the higher CNT content, the CNTs gradually cluster, leading decreased fracture strain and strength. Furthermore, the coated Ni in the CNTs reacts with the magnesium matrix and completely transforms into Mg2Ni, significantly enhancing the interface bonding. This strong interface bonding and the diffusely distributed Mg2Ni in the matrix significantly strengthen the CNT/Mg composite.